South African missions, Methodism, identity and agency in the Cape, with reference to the Klipfontein Mission Station, ca.1800s-2010s - Nel, Annemieke B. (Stellenbosch : Stellenbosch University, 2020)
Thesis (MA)--Stellenbosch University, 2020.